People, Process, and Performance: Setting an agenda for sales enablement research. Issue 3 (2nd July 2020) - Rangarajan, Deva; Dugan, Riley; Rouziou, Maria; Kunkle, Mike
Abstract: Despite being of increasing strategic importance for firms employing B2B salespeople, the concept of sales enablement, and the initiatives it inspires, has heretofore been unexplored by academic sales researchers. This omission is all the more surprising when considering that recent statistics suggest that 61% of firms employing B2B salespeople engage in sales enablement initiatives. The purpose of this agenda setting piece is to introduce the concept of sales enablement to a broader academic audience, and to outline a research agenda for sales researchers. Based on semi-structured, qualitative interviews with practitioners, we propose a framework that suggests that sales enablement can be best understood as a firm-wide strategic initiative that incorporates the 3 Ps of People, Process, and Performance- to deliver value to seller firms and customers alike. Then, we conclude the manuscript by proposing a set of research questions to encourage further academic research into sales enablement.